Effects of aflatoxin B1 contaminated feed on Thai koi (Dhaka University Journal of Biological Sciences, 2019)
The effects of five levels of aflatoxin B1 (0, 25, 50, 100 and 200 ppb) and three (15, 30 and 45 days) culture durations on the growth performances and residue concentration in Thai koi, Anabas testudineus was investigated in indoor plastic tanks. Significant differences were found in 100 and 200 ppb treatment groups in average daily weight gain (ADG, g/d) and specific growth rate (SGR, %/d) compared to those of control, 25 and 50 ppb treatments group. Body muscle in 200 ppb treatment group had significantly higher concentration of aflatoxin B1 (AFB) residue than in the 100 and 50 ppb treatments. Control and 25 ppb treatments group did not have any residue. Total protein and fat contents decreased compared to control, 25 and 50 ppb treatments group. The results suggested that the level of contamination by 50, 100 and 200 ppb aflatoxin B1 in the feed of Thai koi fingerlings may concentrate in the body muscle at a level of above human health hazards. Any feeds with even 50 ppb AFB1 should not be used as feed for raising food fishes.Dhaka Univ. J. Biol. Sci. 28(1): 37-47, 2019 (January)